Method for preparing sodium-ion battery hard carbon negative electrode material by treating biomass with xylanase
The biomass is pre -treated through the pre -processing of the wood polytanase, the components and structures are adjusted, and the hard carbon materials with excellent performance are prepared, and the problem of lack of performance in the existing biomass hard carbon material in sodium cells has achieved high storage. The effect of sodium ability and long cycle life.
Patent Information
- Application Number
- CN202411493909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-25
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The hard carbon materials prepared by existing biomass have problems in sodium ion batteries with poor sodium storage capacity, poor reversible capacity and rate performance, and the existing pretreatment methods require the use of a large number of chemical reagents or have high energy consumption.
By pre -processing the biomass is used to reduce the content of woody polysaccharides in biomass, adjust semi -cellulose content, and then prepare hard carbon materials with excellent performance through high temperature carbonization.
Improving the sodium storage capacity and cycle life of sodium ion batteries, improving the reversible capacity and magnification performance, and simple and environmentally friendly pollution without pollution.
Smart Images

Figure CN119370827A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and specifically relates to a method for preparing a hard carbon negative electrode material for a sodium ion battery by treating biomass with xylanase. Background Art
[0002] With the advancement of science and technology, the demand for energy storage devices such as batteries is gradually increasing. However, the currently commonly used lithium-ion batteries are hindered from commercial application due to their high cost and poor safety. Researchers are committed to finding products with comparable capacity and service life to lithium-ion batteries, lower cost and better safety performance to meet people's daily needs. Through investigation, it was found that sodium-ion batteries are the most promising alternative to lithium-ion batteries. Biomass-based hard carbon has attracted much attention due to its advantages such as rich raw material sources, low cost, easier access, high carbon yield, environmental friendliness and containing multiple elements. Its unique microstructure shows obvious advantages and huge commercial potential among many sodium-ion battery negative electrode materials. However, biomass sources are wide and the consistency is poor, so it is necessary to perform simple regulation through pretreatment to find hard carbon precursors with better performance.
[0003] However, due to the limitations of the components and structural characteristics of biomass precursors, the electrical properties of biomass-based hard carbon materials prepared by direct carbonization are difficult to meet the demand, and existing hard carbon materials prepared from biomass have problems such as poor sodium storage capacity. Therefore, by pretreating the biomass precursor under specific conditions, adjusting and optimizing the components and structure of the biomass precursor, its electrochemical performance is enhanced. However, the hard carbon negative electrode materials prepared by existing methods have the disadvantages of poor reversible capacity and rate performance, and the existing chemical pretreatment methods require the use of a large amount of chemical reagents, which has the problem of difficult post-processing, while the physical method has the problem of high energy consumption. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a hard carbon negative electrode material for a sodium ion battery by treating biomass with xylanase.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a hard carbon negative electrode material for a sodium ion battery by treating biomass with xylanase, wherein the biomass is pretreated with xylanase and then carbonized at high temperature to obtain the hard carbon material.
[0007] The xylanase pretreatment refers to using xylanase to reduce the content of xylan in the biomass. After the xylanase pretreatment, the hemicellulose content in the hard carbon precursor is 10-35wt%. Preferably, when the biomass is walnut shell, the hemicellulose content in the precursor is 18wt%, and the battery performance is the best. When the biomass is corn stalks, the hemicellulose content in the precursor is 20%, and the battery performance is the best.
[0008] The present invention pre-treats biomass by xylanase enzymolysis, adjusts the content of xylan in the biomass, and prepares biomass with different xylan contents; the biomass after enzymolysis treatment is converted into hard carbon after high-temperature carbonization, which can be used as the negative electrode of a sodium ion battery, is green and environmentally friendly, and has excellent performance.
[0009] Preferably, the xylanase is selected from xylanase powder or xylanase liquid.
[0010] Preferably, the pretreatment time is 1 to 48 hours.
[0011] Preferably, the biomass includes walnut shells, corn stalks and the like.
[0012] Preferably, the high-temperature carbonization is a step-by-step carbonization, wherein the first step carbonization temperature is 500°C, the heat preservation time is 1 to 5 hours, and the heating rate is 3 to 8°C / min; the second step carbonization temperature is 1300°C, the heat preservation time is 1 to 5 hours, and the heating rate is 3 to 10°C / min. Too high a carbonization temperature will cause serious graphitization and a decrease in sodium storage capacity.
[0013] Preferably, the specific steps of the above method are as follows:
[0014] (1) breaking the biomass raw materials into small pieces and then grinding them into powder, washing them and drying them for later use;
[0015] (2) adding xylanase into a buffer solution to obtain a xylanase solution;
[0016] (3) mixing the dried biomass raw material with the xylanase solution at an enzyme dosage of 20 to 60 u / g;
[0017] (4) placing the mixed xylanase solution and biomass raw material into a shaker and performing enzymolysis at 40° C. to 60° C. for 1 h to 48 h;
[0018] (5) adding hot water at 60 to 100° C. to the enzymatically hydrolyzed biomass to inactivate the enzyme, and then washing, filtering, and drying to obtain a hard carbon precursor;
[0019] (6) The hard carbon precursor is carbonized at high temperature in a high temperature tube furnace to obtain a hard carbon material.
[0020] Preferably, the mechanical method in step (1) comprises one or more of a wall breaking machine, a ball mill, and a vibration mill.
[0021] Preferably, the biomass in step (1) is crushed to 1-10 mm, and the oven temperature is 70-100° C. for 18-36 hours.
[0022] Preferably, the xylanase in step (3) is produced by fermentation using microorganisms such as fungi or bacteria.
[0023] The enzyme solution is obtained by dissolving xylanase in a citric acid / sodium citrate buffer solution, and the pH of the buffer solution is 5. The enzyme activity of the xylanase enzyme solution is 4-12u / ml.
[0024] The present invention also provides the use of the biomass-based hard carbon prepared by the above method in preparing negative electrode materials for sodium ion batteries.
[0025] The present invention also provides a negative electrode plate for a sodium ion battery, comprising a current collector and an electrode slurry coated on the current collector, wherein the electrode slurry comprises a binder, a conductive agent and the biomass-based hard carbon prepared by the above method.
[0026] Preferably, the conductive agent is conductive carbon black and the binder is sodium carboxymethyl cellulose. Preferably, the electrode slurry is mixed with hard carbon, conductive agent and binder in a mass ratio of 95:3:2. The coating thickness of the electrode slurry on the current collector is 110um, and the coating amount is 2-3mg / cm 2 .
[0027] The present invention also provides a sodium ion secondary battery, comprising the negative electrode plate of the sodium ion battery.
[0028] Beneficial effects of the present invention:
[0029] The present invention removes xylan while retaining cellulose and lignin, which is beneficial to the formation of hard carbon closed pores, and prepares a sodium ion battery hard carbon negative electrode material with excellent performance.
[0030] The present invention is the first to regulate the xylan content in biomass and prepare biomass-based hard carbon precursors with different xylan contents. By regulating the xylan content, hard carbon materials with different porosities and interlayer spacings can be obtained, effectively improving the sodium storage capacity of the battery, which will expand the application of biomass materials in the field of sodium ion negative electrode materials.
[0031] The material provided by the invention has wide sources, low cost and simple process. The sodium ion secondary battery using the material as the negative electrode active material has high operating voltage and energy density, high sodium storage capacity, long cycle life and good safety performance.
[0032] Xylanase treatment of biomass can partially remove hemicellulose, and the lower the hemicellulose content in the biomass, the higher the degree of graphitization of the hard carbon produced. The removal of hemicellulose will affect the degree of cross-linking between lignin, hemicellulose and cellulose, and thus affect the hard carbon structure produced. Moderate removal of hemicellulose can expand the interlayer spacing and facilitate the insertion of sodium ions, but there is an optimal range for treatment. Excessive removal will result in worse performance of the hard carbon.
[0033] The present invention not only has a simpler treatment method and is easy to operate, but also has a low difficulty in process implementation, is green and environmentally friendly, has no pollution, and uses no chemical reagents. The battery performance of the obtained hard carbon material is significantly improved, and the reversible capacity and rate performance are greatly improved, with a capacity improvement of up to 60 mAh / g at a current of 30 mA / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the SEM image of walnut shell powder without enzymatic hydrolysis;
[0035] Figure 2 This is a SEM image of the hard carbon precursor obtained in Example 7;
[0036] Figure 3 TEM image of walnut shell powder without enzymatic hydrolysis;
[0037] Figure 4 This is a TEM image of the hard carbon precursor obtained in Example 7;
[0038] Figure 5 The cycle performance test results of the hard carbon negative electrode material H1 obtained in Example 7;
[0039] Figure 6 This is the battery cycle performance test result of Japan Kuraray's cycle performance.
[0040] Figure 7 It is the reversible capacity of Japan Kuraray, hard carbon material H0, and hard carbon material H1 at a current of 1A / g. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below in conjunction with specific examples. The xylanase used in the examples or comparative examples of the present invention has an enzyme activity of 50,000 u / ml and is purchased from Shandong Longkote Enzyme Preparation Co., Ltd.
[0042] Example 1 to Example 26
[0043] The method for preparing a sodium ion battery hard carbon precursor by treating biomass with xylanase comprises the following steps:
[0044] (1) The biomass raw materials are broken into small pieces and then ground into powder, washed and placed in an oven at 90°C overnight for drying;
[0045] (2) adding xylanase to a prepared citric acid / sodium citrate buffer solution, wherein the pH of the buffer solution is 5, to prepare a xylanase enzyme solution, wherein the enzyme activity of the xylanase enzyme solution is 4u / ml, 8u / ml, or 12u / ml;
[0046] (3) preparing the dried biomass raw material and the xylanase solution at a solid-liquid ratio of 1 g:5 ml;
[0047] (4) placing the mixed xylanase solution and biomass raw material into a shaker and performing enzymolysis at 40° C. to 60° C. for 1 h to 48 h;
[0048] (5) Add 100°C hot water to the enzymatically hydrolyzed biomass sample to inactivate the enzyme, then wash, filter and dry to obtain a hard carbon precursor. The specific enzymatic hydrolysis conditions are listed in Table 1.
[0049] Comparative Example 1
[0050] The method for preparing the hard carbon negative electrode material is the same as that in Example 7, except that mannanase is used for pretreatment.
[0051] Table 1 Enzyme treatment conditions and effects
[0052]
[0053]
[0054] Walnut shell powder that has not been treated with enzymatic hydrolysis, straw powder that has not been treated with enzymatic hydrolysis, and hard carbon precursors of some embodiments and comparative examples were carbonized at high temperature to prepare hard carbon negative electrode materials, and their application performance in sodium ion batteries was tested.
[0055] Preparation of hard carbon negative electrode material: The unenzymatically hydrolyzed walnut shell powder, unenzymatically hydrolyzed straw powder and the obtained hard carbon precursor are carbonized at high temperature in a high-temperature tube furnace to obtain a hard carbon material. The carbonization temperature in the first step of carbonization is 400℃-500℃, the insulation time is 2h, and the heating rate is 5℃ / min; the carbonization temperature in the second step of carbonization is 1100℃-1300℃, the insulation time is 2h, and the heating rate of the high-temperature tube furnace is 5℃ / min. The specific conditions are shown in Table 2.
[0056] The battery performance test method is as follows:
[0057] (1) The hard carbon negative electrode material prepared in the embodiment and the comparative example, the conductive carbon black and the sodium carboxymethyl cellulose were mixed uniformly in a mass ratio of 95:3:2, and then dispersed into an aqueous solution to form a uniform slurry. The slurry was then coated on a copper foil (the coating thickness of the slurry on the current collector was 110 μm) and vacuum dried at 90° C. to obtain a hard carbon electrode sheet.
[0058] (2) Pair the hard carbon electrode sheet in step (1) with the metallic sodium negative electrode, assemble a CR2032 button cell in an inert atmosphere, and test the electrochemical performance of the hard carbon electrode. The electrolyte is 1M NaPF6-EC / EDC (volume ratio 1:1) + 5% FEC. The button cell structure includes a positive electrode shell (stainless steel), a negative electrode shell (stainless steel), a gasket (stainless steel), a hard carbon electrode, a sodium sheet, an electrolyte, and a diaphragm (glass fiber). The test results are shown in Table 2.
[0059] Table 2 Preparation and carbonization conditions of hard carbon materials and properties of hard carbon negative electrode materials
[0060]
[0061]
[0062] From the above results, it can be seen that for walnut shells, the hemicellulose content is about 18wt% when pretreated with xylanase, and the battery performance is optimal when the hemicellulose content is about 20wt% when pretreated with xylanase. Excessive use of xylan will cause waste, and the hemicellulose removal effect produced by it cannot be fully utilized, while too little use will lead to insufficient hemicellulose removal, resulting in no obvious improvement in battery performance. Compared with the prior art, the first coulomb efficiency is higher, and the pretreatment method is more green and environmentally friendly, and pollution-free.
[0063] Figure 1 This is the SEM image of walnut shell powder without enzymatic hydrolysis. Figure 2 is a SEM image of the hard carbon precursor obtained in Example 7; Figure 1 and Figure 2 By comparison, it can be seen that after using xylanase to remove part of the hemicellulose, the porosity of the walnut shell increases, which is conducive to the formation of closed pores during the carbonization process and increases its sodium storage capacity. Figure 3 This is the TEM image of walnut shell powder that has not been enzymatically treated. Figure 4 This is the TEM image of the hard carbon precursor obtained in Example 7; it can be observed from the TEM electron microscope that moderate removal of hemicellulose can expand the interlayer spacing, which is beneficial to the insertion of sodium ions and increases its rate performance, and removal of hemicellulose is beneficial to the formation of carbon layers, which is beneficial to the increase of closed pores and its sodium storage capacity. Figure 5 The cycle performance test results of the hard carbon negative electrode material H1 obtained in Example 7 are as follows: Figure 6 This is the battery cycle performance test result of Japan Kuraray. Figure 5 and Figure 6 It can be seen that the capacity of the sample in Example 7 is much higher than that of Japan Kuraray, and can still reach more than 90% after 100 cycles. The sodium storage performance and cycle performance under large current are better than those of Japan Kuraray products. Figure 7It is the reversible capacity of Japan Kuraray, hard carbon material H0, and hard carbon material H1 at a current of 1A / g.
Claims
1. A method for preparing a hard carbon negative electrode material for a sodium ion battery by treating biomass with xylanase, characterized in that: The biomass was pretreated with xylanase and then carbonized at high temperature to obtain hard carbon material.
2. The method according to claim 1, characterized in that After pretreatment with xylanase, the hemicellulose content in the biomass was 10-35 wt%.
3. The method according to claim 1, characterized in that The xylanase is selected from xylanase powder or xylanase liquid. Preferably, the enzyme treatment time is 1 to 48 hours.
4. The method according to claim 1, characterized in that: The biomass includes walnut shells, corn stalks and the like.
5. The method according to claim 1, characterized in that The high-temperature carbonization is a step-by-step carbonization, wherein the first step carbonization temperature is 500°C, the heat preservation time is 1 to 5 hours, and the heating rate is 3 to 8°C / min; the second step carbonization temperature is 1300°C, the heat preservation time is 1 to 5 hours, and the heating rate is 3 to 10°C / min.
6. The method according to claim 1, characterized in that The specific steps of the above method are as follows: (1) breaking the biomass raw materials into small pieces and then grinding them into powder, washing them and drying them in an oven for later use; (2) adding xylanase to the prepared buffer solution to prepare a xylanase solution; (3) preparing the dried biomass raw material and the xylanase solution at an enzyme dosage of 20 to 60 u / g; (4) placing the mixed xylanase and biomass raw material into a shaker and performing enzymolysis at 40° C. to 60° C. for 1 h to 48 h; (5) adding 60-100° C. hot water to the enzymatically hydrolyzed biomass sample to inactivate the enzyme, and then washing, filtering, and drying to obtain a hard carbon precursor; (6) The hard carbon precursor is carbonized at high temperature in a high temperature tube furnace to obtain a hard carbon material.
7. The method according to claim 6, characterized in that The mechanical method in step (1) includes one or more of a wall breaker, a ball mill, and a vibration mill. Preferably, the biomass in step (1) is broken into 1-10 mm. The oven temperature is 70-100° C. for 18-36 hours. Preferably, the xylanase in step (3) is selected from microorganisms such as fungi or bacteria for fermentation production.
8. Use of the biomass-based hard carbon prepared by the method according to any one of claims 1 to 7 in preparing negative electrode materials for sodium ion batteries.
9. A negative electrode plate for a sodium ion battery, characterized in that: include: A current collector, a binder coated on the current collector, a conductive agent and the biomass-based hard carbon prepared by the method according to any one of claims 1 to 7.
10. A sodium ion secondary battery, characterized in that: A negative electrode sheet of a sodium ion battery comprising the method of claim 9.
Citation Information
Patent Citations
Preparation method of activated carbon
CN102134069A
Preparation method and application of biomass hard carbon sodium ion battery negative electrode material
CN117246997A
Preparation method of cellulase hydrolyzed corncob-based hard carbon negative electrode material
CN117735520A
Lignin-based hard carbon negative electrode material with high rate capability as well as preparation and application of lignin-based hard carbon negative electrode material
CN117985681A
Biomass-based hard carbon material as well as preparation method and application thereof
CN118289733A